PERAN PENGAWAS PENDIDIKAN AGAMA ISLAM (PPAI) DALAM MENINGKATKAN KOMPETENSI GURU PAI DI SMP SWASTA WILAYAH KECAMATAN SIDOARJO KABUPATEN SIDOARJO - Laila Nuzulul Fitria Noor; Kharisul Wathoni (MA'ALIM: Jurnal Pendidikan Islam, 2020)
Supervisor of Islamic Education is one component that has an important role in improving the quality of education. The tasks of the supervisor of Islamic education is to improve the competence of Islamic education teachers in schools to produce quality and professional teachers. This study aims to determine what is the role of Islamic education supervisors in improving pedagogical competence and professional competence of Islamic education teachers in Private Junior High School in District of Sidoarjo, Sidoarjo. The researcher used a qualitative approach with collection data methods such as interviews, observation, and documentation. Data analysis method used an interactive model (plot) of Miles and Huberman which includes data reduction, data display, and conclusion or verification. From the results of the study it was found that the role of the supervisor of Islamic education in improving the pedagogical competence of Islamic Education teachers in Private Junior High School in District of Sidoarjo, Sidoarjo had been done well through several ways such as supervision in learning planning, ability in student learning processes and outcomes, ability to utilize resources learning, the ability to develop student potential. Whereas the role of the supervisor of Islamic education in enhancing the professional competence of Islamic Education teachers in Private Junior High School in District of Sidoarjo, Sidoarjo has been fulfilled through several ways, namely providing assistance for teachers in preparing RPP and monitoring of teaching and learning activities in the classroom.